Research Note: Does Crime Deter UK Tourists from Visiting Trinidad and Tobago?. (August 2013) - Saridakis, George; Sookram, Sandra; Mohammed, Anne-Marie
In this paper the deterrent effect of crime on tourism in Trinidad and Tobago is investigated using annual data for the period 1978– 2007 and focusing on the UK source market. The findings indicate that both property crime and violent crime have devastating long-run effects on the tourism sector. The authors also find that income, the price of tourism and transportation costs have significant impacts.